Early Childhood Cholestasis, Causes & Associated Factors in Children - Y. Mahmood , Adnan; I. Alezzi, Jalil; Jwad Dawod, Haider; Aidah Bin Mohanna, Mabrook (Diyala Journal of Medicine, 2024)
Background: Newborn cholestasis is explained as a persisted rise of the serum conjugated bilirubin outside the first two weeks of life. There are many etiologies of newborn cholestasis that must be differentiated since immediate interference may give a better outcome. Objective: Newborn cholestasis is explained as a persisted rise of the serum conjugated bilirubin outside the first two weeks of life. There are many etiologies of newborn cholestasis that must be differentiated since immediate interference may give a better outcome. Patients and Methods: A cross-sectional research of forty-eight children consulting the Childhood Wellbeing Teaching Hospital in Baghdad/Medical City from 1st of November 2018 to the 30th of November 2021, complete evaluation by full history, physical checkup and laboratory studies. Cholestasis was demarcated as an extended raise of the levels of conjugated bilirubin outside the 1st 2 weeks of age above 1.0mg/dl(17.1µmol/l) if the whole serum bilirubin(TSB) is <5.0 mg/dL or above 20% of the TSB if the TSB is >5.0 mg/dl. Results: Out of 48 children involved in the study ,62.5% resided in Baghdad, and the remainder was belonged to other districts. The mean age of children was 11.1 months. The males constituted 58.3% of them. Eleven cases (22.9%) were caused by congenital infection, nine 18.8% had no cause detected, while 16.7% caused by biliary atresia and 16.7% had unidentified etiology, however 10.4% was related to sepsis. Biliary atresia was more frequent in boys in 62.5% compared to 37.5% in females. Family history was positive only in11.1% of idiopathic neonatal hepatitis. It was found that 81% of cholestatic jaundice were caused by congenital infection. In comparison, 62.5% caused by biliary atresia and 60% caused by sepsis appeared on the second week of the child's age, and this difference was significant statistically P-value 0.01. Conclusion: Innate infections are the most frequent source, where CMV contagion is the most commonly detected. Clinical findings included clay colored stool & elevated alkaline phosphatase concentrations observed primarily on biliary atresia. There are no specific test to identify the etiology of newborn cholestasis.